EVALUASI MODAL KERJA DAN PROFITABILITAS - Eka Yudhyani3, Tengku Syahfira Muthia Elfreda Aplonia Lau2 (EKONOMIA, 2016)
This study aims to determine whether the working capital which predetermined CV. Koki Teppanyaki have given the increase in profitability. Used theoretical basis of management accounting, working capital, and profitability. Hypotesis : working capital predetermined CV. Koki Teppanyakihas profided an increase in profitability. The data used are financial statements for 2012 - 2013. Analysis tool used is as follows : 1. The working capital consists of 3 phases : 1. Working capital turnover, 2. Sales forecast phase, and 3. Working capital requirements. 2. Profitability consists of 2 ratios : Return On Investment and Net Profit Margin. For working capital research done by calculating working capital turnover, sales forecasts, and working capital requirements. While the profitability of research conducted by calculating return on investment and the net profit margin for the year 2012 – 2013. Then look for changes and growth of the ratio of proficiency level, then known causes of changes in the level of profitability CV. Koki Teppanyaki period 2012 – 2013. The conclusions of the research working capital requirements CV. Koki Teppanyaki show that working capital available at the end of 2013 amounted to Rp. 130.584.550 working capital is not sufficient for the next period in 2014, amounting to Rp. 174.778.500, in which the difference value is Rp. 44.193.950. Whereas the the level of profitability in CV. Koki Teppanyaki period 2012 – 2013 decreased the net profit margin in 2013 of 1.85%, and an increase in the return on investment in 2013 amounted to 59.79%. Of research findings should be to facilitate the operations of the company should CV. Koki Teppanyaki financial companies particularly regarding the calculation of working capital is to conduct planning and controlling working capital carefully and thoroughly